2005
DOI: 10.1103/physreve.71.051303
|View full text |Cite
|
Sign up to set email alerts
|

Jamming during the discharge of granular matter from a silo

Abstract: In this work, we present an experimental study of the jamming that stops the free flow of grains from a silo discharging by gravity. When the outlet size is not much bigger than the beads, granular material jams the outlet of the container due to the formation of an arch. Statistical data from the number of grains fallen between consecutive jams are presented. The information that they provide can help one to understand the jamming phenomenon. As the ratio between the size of the orifice and the size of the be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
277
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(296 citation statements)
references
References 14 publications
17
277
2
Order By: Relevance
“…It has been shown that for big sizes of the outlet orifice the outpouring is almost continuous, while for a small orifice jamming events can occur. The border between the two regimes is sharply defined at R c ≈ 5, where R is the ratio between the diameter of the outlet orifice and the diameter of the beads [14]. For R > R c , the flow can be measured just by dividing the number of fallen beads by the time elapsed.…”
Section: Three-dimensional Silomentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that for big sizes of the outlet orifice the outpouring is almost continuous, while for a small orifice jamming events can occur. The border between the two regimes is sharply defined at R c ≈ 5, where R is the ratio between the diameter of the outlet orifice and the diameter of the beads [14]. For R > R c , the flow can be measured just by dividing the number of fallen beads by the time elapsed.…”
Section: Three-dimensional Silomentioning
confidence: 99%
“…The experimental setup for the three-dimensional silo was described in detail in a former article [14]. It consists of an All the beads are spherical scaled, automated cylindrical container with an orifice in the base.…”
Section: Three-dimensional Silomentioning
confidence: 99%
“…Familiar examples of clogging appear in crowd stampedes [9,10], fluid-driven particle flows [11,12], and granular materials. In this later case, abundant research has been carried out covering 2D [13,14] and 3D [15,16] silos, inclined outpouring [17,18], silos with an obstacle above the outlet [19], anisometric (wedge) hoppers [20], and piles discharged through an orifice at their bottom [21]. In all these systems clogging arches withstand the weight of the particles above them just as architectural arches do.…”
mentioning
confidence: 99%
“…Quantitative predictions for flow rates were proposed (e. g. [5][6][7][8] and references therein). When the outlet diameter is smaller than about 5 particle diameters [9][10][11][12][13], clogs form after some time at the orifice and block further outflow, mostly unwanted. Spontaneous arch formation [14,15], the preceding kinetics [16], as well as the inherent force distributions [17,18] have been analyzed in the literature.…”
mentioning
confidence: 99%